Factors associated with caregiver ability to support medication adherence among people with mental disorders: a multivariate cross-sectional study - Andriani, Andriani; Yusuf, Ah; Fitryasari, Rizki; Basrah, Miftahul Jannah; Arsyad, Dian Sidik; Hariati, Suni; Erfina, Erfina; Nurmaulid, Nurmaulid; Kadar, Kusrini S. (Jurnal Ners, 2026)
Introduction: This study aimed to identify family, caregiver, patient, nurse, and healthcare service factors associated with caregivers’ ability to support medication adherence among relatives with mental disorders. Methods: This cross-sectional study was conducted between February and June 2024 at seven community health centers (Puskesmas) in Makassar, Indonesia. Purposive sampling was used to recruit 155 caregivers. Questionnaires were validated prior to data collection. Bivariate associations were examined using the chi-square test, and factors associated with caregivers’ ability to support medication adherence were analyzed using multivariate logistic regression. Results: The multivariate model was statistically significant (model χ²  =  42.87, p < 0.001; Nagelkerke R² = 0.32). In bivariate analyses, the caregiver’s ability to support patients’ medication adherence was associated with family functioning, caregiver factors (gender, stress, motivation, knowledge), patient factors (relapse frequency, severity level), and nurse psychological factors. In the multivariate analysis, family economic status (AOR = 0.22, 95% CI = 0.07–0.69, p = 0.010), family functioning (AOR  =  2.58, 95% CI = 1.19–5.58, p = 0.016), caregiver motivation (AOR = 0.29, 95% CI = 0.12–0.73, p = 0.008), and caregiver knowledge (AOR = 0.40, 95% CI = 0.16–0.96, p = 0.041) remained significantly associated with caregiver ability to support medication adherence. Conclusions: These results suggest that family factors and caregiver psychosocial preparedness play critical roles in facilitating adherence-related caregiving practices. Strengthening family functioning and caregiver motivation and knowledge may improve support for medication adherence.